IMPLEMENTASI AKUNTANSI DALAM KEHIDUPAN MENURUT PERSPEKTIF ISLAM - Budi Gautama Siregar (Institut Agama Islam Negeri Padngsidimpuan, 2015)
Abstract Accounting in Islamic view is a method Accounting in Syariah's concept Islam which is default law basic and permanent, one that is concluded from Syariah's sources Islams and is used as order by an Accountants in its work, well in book keeping, analisis, measurement, explanation, and also explanation, and becomes footing in words an instance or scene. Accounting constitutes domain muamalah in Islamic study. Its mean is turned over to ability minds man to develop it. But since the importance of the problem this there for Allah SWT even give it place in al-Qur's innocent book ’ an, alBaqarah is sentence 282. This sentence as symbol of economic that have nature of accounting one that gets dianalogkan with double is entry , and figures balance or balance number. Accountings developmental thus Islamic, point level with another, sincerity and justice have in practice been actualized accounting. Kata Kunci : Akuntansi, Kehidupan, Islam